Design and Development of a Web-Based Production Management Information System to Support Digital Entrepreneurship in Furniture Manufacturing: A Case Study of Prima Furniture Bandung - Yogi Eka Nurdiansyah; Irfan Dwiguna Sumitra; Ganieva Nasiba Shukhrat Kizy (International Journal of Research and Applied Technology (INJURATECH), 2026)
For small and medium-sized furniture makers, production management is still often done manually, with spreadsheets and instant-messaging chats, leaving order tracking, work scheduling and operator wage calculation vulnerable to delay, miscommunication and recording errors. A web-based production management information system for a made-to-order furniture factory is designed and built in this project. It handles sales order intake, work-order tracking through cutting, assembly and finishing, delivery and driver management and piece-rate salary computation and adds a natural-language analytics assistant to query production and sales data. Development was carried out using the Prototyping model. The cycle of communication, rapid planning, rapid design, prototype manufacturing and deployment with feedback was well suited to a scenario where requirements constantly changing on the factory floor rather than being fixed upfront. Requirements were extracted from direct observation and informal discussions with the owner and production operators, and were modelled as business-process (as-is/to-be), use case, and entity-relationship diagrams prior to implementation on a relational database with a web front end. The system was tested with blackbox testing of its core modules and a System Usability Scale (SUS) questionnaire filled out by five respondents representing the positions of administrator, sales, and production-supervisor. All the functions evaluated gave the desired outcome and the SUS score of 80.0 falls in the “Good” usability band. The results suggest that a prototyping-based web platform can pull scattered, manual furniture-production records into one real-time system, cutting recording effort, making order status traceable from intake to delivery, and giving the case-study business a firmer footing for continued growth as a digitally run enterprise